Training on professional foreign language for students of engineering specialties: implementation of electronic technology - Sergei V.Smirnov; Aygul Z. Ibatova (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
The purpose of our work is to check the effectiveness of the principle of systematic in the process of teaching professional foreign language to the engineering specialties. The laboratory work contains information lexical programs for the introduction of active lexical lessons, vocabulary and grammar exercises, and questions to the texts of lessons, designated for self-control and mutual control. The authors presented the results of the implementation of the system principle in the pedagogical process, namely the possibility of providing systematic construction of methodical literature and construction of intra subject links. The laboratory work, thanks to which there is an actualization and improvement of basic knowledge and skills, as well as the motivation of educational activity - is the form of realization of this principle. The students have an opportunity to demonstrate the independence in performing communicative actions in the professional sphere, provided by the program, to automate their skills, to conduct the self-study and self-monitoring of knowledge and skills, as well as to make their correction.